The role of nitride species in the gas-phase furfural hydrogenation activity of supported nickel catalysts - Jiménez-Gómez, Carmen Pilar; Defilippi, Chiara; Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús; Giordano, Cristina (Elsevier B.V., 2020)
A series of C-rich nickel nitride nanoparticles supported on silica has been prepared by the urea glass route, with urea as nitrogen and carbon source, and characterized by different physico-chemical techniques. They consist of Ni3N nanoparticles of 20-25 nm embedded into a carbonaceous matrix. These catalysts are much more active and stable than a nickel supported silica catalyst, which drastically deactivates. The supported Ni3N catalyst, with a 10 wt.% Ni, maintained a furfural conversion higher than 80% after 5 h of time-on-stream, at 170 ⁰C, with a high WHSV of 6 h-1. Complete initial furfural conversion values were observed at reaction temperatures varying from 170 to 230⁰C, and the selectivity toward furan and furfuryl alcohol (decarbonylation and hydrogenation products, respectively) was tuned by varying this temperature. After the catalytic tests, XPS and XRD have demonstrated that nanoparticles are stable, although carbonaceous deposits were also detected.
Keywords: Catálisis; Catalizadores; Biomasa - Combustibles; Aldehídos; Nickel nitride; Furfuryl alcohol; Hydrogenation; Furfural; Biorefinery